Coupled aerothermal-mechanical analysis in single crystal double wall transpiration cooled gas turbine blades with a large film hole density. (25th January 2023) - Courtis, Matthew; Skamniotis, Christos; Cocks, Alan; Ireland, Peter
Highlights: Double wall transpiration cooling protects turbine blades against high heat flux. A high film hole density can benefit both the aerothermal and mechanical response. The wall spacing influences the cooling effectiveness and aerothermal response. The wall thickness ratio influences thermal stresses and the mechanical response. Stresses tend to apply along secondary crystallographic directions around features. Abstract: The ambition for increasing gas turbine efficiency beyond current levels through the elevation of gas temperatures demands substantial progress in turbine blade cooling technology. Double wall transpiration cooling (DWTC) is an emerging technology which offers enhanced thermal protection at only modest coolant flows, thanks to a combination of impingement jets and densely packed arrays of film cooling holes. This paper presents a coupled aerothermal-mechanical investigation of a transpiration cooled double wall turbine blade design, by employing Computational Fluid Dynamics (CFD), heat transfer theory as well as stress analysis based on plate theory and Finite Element (FE) analysis. In comparison to previously explored systems with modest outer wall porosity, a system with high porosity is found to display enhanced cooling effectiveness and to reduce the temperature difference across the two walls that drives thermal stresses. This difference can be decreased further by reducing the wall spacing, H, or the inner-outer wall thickness ratio, t c / t h, at the cost of higher overall metal temperatures. A lower bound for H should be used to avoid undesirable poor coolant flow distribution and hot gas ingestion effects, whereas the t c / t h ratio does not impose any aerothermal constraints. Thermal stresses associated with a fixed temperature field are invariant with H but they vary drastically with t c / t h . From a design perspective, the above suggest that H is primarily determined by aerothermal requirements, whereas t c / t h by the mechanical performance. The single crystal orientation and elastic anisotropy of Nickel alloys are shown to have a profound impact on the stress concentration around cooling holes, with secondary crystallographic directions, such as 〈 110 〉 and 〈 111 〉, playing a prominent role in the local stress state. Our study provides a framework for optimising the aerothermal and mechanical performance in a range of high temperature components and highlights key areas where more elaborate analysis is needed.